2012
DOI: 10.1093/bja/aes263
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary exercise testing predicts 5 yr survival after major surgery

Abstract: Multivariate analysis and model generation techniques can be applied to CPET data to predict 5 yr survival after major surgery more accurately than is possible with single variable analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…Although oxygen uptake efficiency slope values were found to be strongly correlated with peak oxygen uptake and the ventilatory anaerobic threshold, the small intra-individual differences in maximal and submaximal values might limit the clinical utility of this measure; this requires further research. Future research should also address the prognostic value of the oxygen uptake efficiency slope for different postoperative outcomes in major abdominal surgery, as only one study [32] evaluated the predictive value of the oxygen uptake efficiency slope; this focused on mortality. From the latter study, it is unclear whether the authors normalised absolute oxygen uptake efficiency slope values for body mass, which we believe is necessary, just as with peak oxygen uptake and the ventilatory anaerobic threshold.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Although oxygen uptake efficiency slope values were found to be strongly correlated with peak oxygen uptake and the ventilatory anaerobic threshold, the small intra-individual differences in maximal and submaximal values might limit the clinical utility of this measure; this requires further research. Future research should also address the prognostic value of the oxygen uptake efficiency slope for different postoperative outcomes in major abdominal surgery, as only one study [32] evaluated the predictive value of the oxygen uptake efficiency slope; this focused on mortality. From the latter study, it is unclear whether the authors normalised absolute oxygen uptake efficiency slope values for body mass, which we believe is necessary, just as with peak oxygen uptake and the ventilatory anaerobic threshold.…”
Section: Figurementioning
confidence: 99%
“…One such parameter, the oxygen uptake efficiency slope (OUES), has been reported to have prognostic value in predicting major cardiac events and mortality in patients with heart failure and coronary artery disease [14][15][16][17]. To the best of our knowledge, only one study investigated the predictive value of the oxygen uptake efficiency slope for a 5-year survival period after a major surgery, and concluded that it did not appear to be a strong predictor of mortality [32]. Baba et al [18] introduced and validated a logarithmic transformation of the minute ventilation over the entire exercise period, resulting in a linear relationship between the minute ventilation and oxygen uptake during the entire, and especially the last part, of the cardiopulmonary exercise test.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor exercise capacity in surgical patients, as measured objectively by preoperative cardiopulmonary exercise [612], is associated with poorer postoperative outcomes—including infection—following surgery [13]. Plausible mechanisms that explain the link between poor exercise capacity and poorer postoperative outcomes remain underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The AT has been extensively investigated, and the findings in the present study of a worse outcome at a lower AT is in keeping with previous work. A lower AT is associated with a longer overall LOS [7,9,12,[18][19][20], increased incidence of adverse cardiac events [3] and poorer overall survival [6,[8][9][10]. Several other studies have also found an increased incidence of severe complications in patients who have a poor performance on CPET [7,12,[20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%